Synthesis, Superoxide Dismutase Mimetic and Anticancer Activities of Metal Complexes of 2,2-Dimethylpentanedioic Acid(2<small.letters>dmepda</small.letters>H 2 ) and 3,3-Dimethylpentanedioic acid(3<small.letters>dmepda</small.letters>H 2 ): X-Ray Crystal Structures of [C<small.letters>u</small.letters>(3<small.letters>dmepda</small.letters>)(<small.letters>bipy</small.letters>)] 2 ⋅ 6H 2 O and [C<small.letters>u</small.letters>(2<small.letters>dmepda</small.letters>)(<small.letters>bipy</small.letters>)(E<small.letters>t</small.letters>OH)] 2 ⋅4EtOH( bipy=2, 2 ′ Bipyridine) (Bioinorganic Chemistry and Applications)
2,2-dimethylpentanedioic acid (2dmepda H 2 ) and 3,3-dimethylpentanedioic acid (3dmepda H 2 ) reacted with copper(II) acetate to give [Cu(2dmepda) ( H 2 O ) 3 ] 2 (1) and [Cu(3dmepda) ( H 2 O ) 3 ] 2 (2). Reaction of (1) and (2) with 1,10-phenanthroline and 2, 2 ′ -bipyridine yielded [Cu(2dmepda)(phen) ( H 2 O ) ] 2 0.5phen (3), [Cu(2dmepda)(bipy) ( H 2 O ) ] 2 (4), [Cu(2dmepda)(bipy)(EtOH)] 2 ⋅2EtOH (4A), [Cu(3dmepda)(phen) ( H 2 O ) ] 2 (5), and [Cu(3dmepda)(bipy) ( H 2 O ) ] 2 ⋅ (6). The structures of (4A) and (6) each consists of a [Cu(bipy)(dicarboxylate) ( solvent ) ] 2 dimer. The superoxide dismutase (SOD) mimetic activity of the novel copper complexes and their manganese analogues was investigated. The dimethyl sulphoxide(DMSO) soluble complexes (1)–(4) and (6) were assessed for their cancer chemotherapeutic potential towards hepatocellular carcinoma and kidney adenocarcinoma cell lines. The 1,10-phenanthroline containing complex [Cu(2dmepda)(phen) ( H 2 O ) ] 2 0.5phen (3) was the most potent with activity that compares well to that of <emph>cis</emph>platin.